2010
DOI: 10.1016/j.ydbio.2009.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosome positioning: How is it established, and why does it matter?

Abstract: Packaging of eukaryotic genomes into chromatin affects every process that occurs on DNA. The positioning of nucleosomes on underlying DNA plays a key role in regulation of these processes, as the nucleosome occludes underlying DNA sequences. Here, we review the literature on mapping nucleosome positions in various organisms, and discuss how nucleosome positions are established, what effect nucleosome positioning has on control of gene expression, and touch on the correlations between chromatin packaging, seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
244
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(268 citation statements)
references
References 102 publications
23
244
0
1
Order By: Relevance
“…Explaining two correlated molecular functions-histone binding and transcriptional regulation-in the same sequence segment may be seen as a chicken-and-egg problem (6)(7)(8)(9). Is transcription factor binding the primary function, which displaces nucleosomes to sequence segments in which transcription is neutral or deleterious?…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Explaining two correlated molecular functions-histone binding and transcriptional regulation-in the same sequence segment may be seen as a chicken-and-egg problem (6)(7)(8)(9). Is transcription factor binding the primary function, which displaces nucleosomes to sequence segments in which transcription is neutral or deleterious?…”
mentioning
confidence: 99%
“…Several mechanisms are known to influence the local probability of nucleosome formation (8). Histone-affine DNA has a specific nucleotide composition that facilitates superhelical turns around the cylinder-shaped octamer (10,11).…”
mentioning
confidence: 99%
“…The wrapping of the DNA around the histone octamer protein core in the nucleosome impedes the access of transcription factors to the DNA sequence information. Thus, changes of nucleosome positions at promoter and enhancer regions may directly affect gene expression (1)(2)(3)(4). To control nucleosome positions (and with it the access to the associated DNA), a complex chromatin remodeling machinery operates in the eukaryotic cell nucleus.…”
mentioning
confidence: 99%
“…In Saccharomyces cerevisiae, genomewide mapping of nucleosomes suggests that only a few DNA sequence-based properties such as absence of A/T rich regions, or conversely a high G/C content, have a strong effect on general positioning (discussed in Hughes and Rando 2009;Tillo and Hughes 2009;Radman-Livaja and Rando 2010;Zhang et al 2010), so the dominant mechanism for defining the location of nucleosomes may be statistical positioning (Gkikopoulos et al 2011;Zhang et al 2011). Earlier individual nucleosome mapping approaches in S. cerevisiae at single sites had already shown that barrier effects provided a major positioning effect, with DNA properties and histone-DNA interactions acting to fine tune local accessibility and behaviour (Thoma 1992).…”
Section: In Vivo Positioning As Combination Of Effectsmentioning
confidence: 99%
“…The energetics of these deformations gives rise to sequence specific effects on DNA binding, and many authors have addressed the question of how they are linked with choice of nucleosome position (see Segal and Widom 2009a;Travers et al 2009;Radman-Livaja and Rando 2010;Olson and Zhurkin 2011;Trifonov 2011;Zhurkin 2011;Chua et al 2012).…”
Section: Dna Conformation In the Nucleosomementioning
confidence: 99%